Vocabulary Enrichment for Students of Indonesian for Foreign Speakers (BIPA) Through the Enuma School Application - Widya Arfiyanti Puspa Sari; Jamaluddin Nasution; Agita Karina Sinulingga; Sadar M. Rajagukguk; Tuty Susianti Sihombing (JELT : Journal of English Education, Teaching and Literature, 2025)
This research discusses the potential application of Enuma School as a tool to aid in the enrichment of Indonesian vocabulary for BIPA (Bahasa Indonesia untuk Penutur Asing) learners. Using a qualitative approach, the study analyzes the interactive features and contextual content offered by the application. The analysis results indicate that Enuma School can serve as an effective alternative digital application for developing Indonesian vocabulary, enhancing BIPA students' motivation to learn through educational games, supporting independent learning, and fostering digital literacy. However, challenges such as integration with the BIPA curriculum, training for educators, evaluating the effectiveness of the application's use, and addressing technology accessibility gaps need to be considered. This study suggests that educational institutions consider using this application as part of their BIPA learning strategy to achieve better outcomes in mastering Indonesian vocabulary.